Application of digital practice to improve head movement, visual perception and activities of daily living for subacute stroke patients with unilateral spatial neglect: Preliminary results of a single-blinded, randomized controlled trial. Issue 6 (12th February 2021) - Choi, Ho-Suk; Shin, Won-Seob; Bang, Dae-Hyouk
Abstract: Background: Virtual reality (VR) based digital practice is an attractive way to provide a patient engagement, motivation and adaptable environment for stroke rehabilitation. However, clinical evidence of efficacy with VR-based digital practice is very limited. In this study, we investigated the effects of VR-based digital practice program on unilateral spatial neglect (USN) rehabilitation in patients with subacute stroke. Methods: Twenty-four subacute stroke patients with USN were enrolled and randomly assigned to digital practice group (n = 12) and control group (n = 12). Patients in digital practice group received training programs with VR-based applications with leap motion environment. Control group received conventional USN specific training programs. All patients were underwent 4 week practice program (3 sessions/week, a half-hour/session). We analyzed training effects before and after training by assessing the line bisection test, Catherine Bergego Scale, modified Barthel index, Motor-Free Visual Perception Test Vertical Version (MVPT-V), and horizontal head movements (rotation degree and velocity during the VR-based applications), and compared the results between the two groups. Results: Compared to control group, digital practice group showed significantly greater improvements in the line bisection test ( P = .020), and visual perceptual tasks (MVPT-V, responded more on left visual task, P = .024; correctly respond more on both left and right visual tasks, P = .024 and P = .014, respectively; and faster response time, P = .014). Additionally, horizontal head movement of rotation degree and velocity during the VR based practice in the digital practice group were significantly increased more than control group (P = .007 and P = .001, respectively). Conclusions: VR-based digital practice program might be an affordable approach for visual perception and head movement recovery for subacute stroke patients with USN.